Exclusive Breastfeeding Practices among Female Healthcare Workers and Child Welfare Clinic Mothers in the Sissala East Municipality of Ghana - Dinwia, Jonas; Wireko, Sabina Ampon- (South Asian Journal of Social Sciences and Humanities, 2024)
Babies, mothers, and society as a whole all benefit greatly from exclusive breastfeeding. Babies  who are breastfed alone are protected from harmful bacteria that can be found in formula and other  infant meals, bacteria that can cause diarrhoea, other illnesses, and even death. The study  investigated exclusive breastfeeding practices among female healthcare workers and child welfare  clinic mothers in the Sissala East Municipality of Ghana. A facility-based quantitative descriptive  cross-sectional design was used in this study. Twenty-five lactating mothers were purposively  selected using a simple random technique. Data was collected using a closed-ended questionnaire  and data analysis using IBM SPSS version 21.0. The results showed that mothers whose income  ranged from 500 cedis to 1000 cedis were 3.29 times more likely to breastfeed exclusively  compared to those whose income was not up to 500 cedis (COR:3.29 (C.I:1.11 – 9.71) P=0.031).  Those in other professional groups were 43% less likely to practice exclusive breastfeeding than  those who were health workers.
Keywords: Exclusive; Breastfeeding; Child welfare; Mothers